2023
DOI: 10.3390/s23063346
|View full text |Cite
|
Sign up to set email alerts
|

Binding of SARS-CoV-2 Structural Proteins to Hemoglobin and Myoglobin Studied by SPR and DR LPG

Abstract: One of the first clinical observations related to COVID-19 identified hematological dysfunctions. These were explained by theoretical modeling, which predicted that motifs from SARS-CoV-2 structural proteins could bind to porphyrin. At present, there is very little experimental data that could provide reliable information about possible interactions. The surface plasmon resonance (SPR) method and double resonance long period grating (DR LPG) were used to identify the binding of S/N protein and the receptor bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The method was successfully applied for SARS CoV-2 structural proteins detection [8,9]. The optical set-up used for amplitude SPR detection is shown in figure 1.…”
Section: Surface Plasmon Resonance Methodsmentioning
confidence: 99%
“…The method was successfully applied for SARS CoV-2 structural proteins detection [8,9]. The optical set-up used for amplitude SPR detection is shown in figure 1.…”
Section: Surface Plasmon Resonance Methodsmentioning
confidence: 99%
“…39 Furthermore, a conceptual model predicted that motifs from SARS -CoV -2 structural proteins could bind to porphyrin, whereas experimental data indicated that the S/N protein binds to hemoglobin and myoglobin. 40 Myoglobin is a well -known offender in the pathogenesis of AKI, which emphasizes the COVID -19-myoglobin-AKI interactions.…”
Section: Model -Building Processmentioning
confidence: 99%
“…Interestingly, SARS-CoV-2 structural proteins in COVID-19, including the S, M, and N proteins, can accumulate in the blood in a complex with hemoglobin and its metabolites [12,13]. The S protein can hyperactivate immune cells via Toll-like receptors [14].…”
Section: Introductionmentioning
confidence: 99%